2008
DOI: 10.1387/ijdb.072549dd
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural analysis of egg membrane abnormalities in post-ovulatory aged eggs

Abstract: Microscopic analyses of mammalian gamete ultrastructure have provided among the most seminal insights into fertilization. Here we present a summary of ultrastructural studies of mammalian fertilization, together with a review of the effects of post-ovulatory aging in eggs, and our own results using scanning electron microscopy to examine the effects of post-ovulatory aging on the egg membrane topography. Our previous work detected two abnormalities in egg membrane function in aged eggs: aged eggs appeared to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 73 publications
0
13
0
Order By: Relevance
“…Postovulatory aging is associated with unsuccessful fertilization and, in instances when aged eggs are fertilized, with poor reproductive outcomes, including pregnancy loss, smaller litter sizes, or in offspring with abnormalities [14,15,90,91]. Relevant to the data here, postovulatory aged eggs have reduced MAPK3/1 activity associated with a range of membrane and cortical abnormalities and the above-mentioned propensity to undergo parthenogenetic activation [92][93][94][95][96][97][98][99][100]. Thus, what we observe here with MAPK3/1 pathway inhibition and the associated reduction in myosin-II function is consistent with changes that occur with postovulatory aging, suggestive of a tie between reduced MAPK3/1 activity and several of the changes observed in aged eggs.…”
Section: Discussionmentioning
confidence: 84%
“…Postovulatory aging is associated with unsuccessful fertilization and, in instances when aged eggs are fertilized, with poor reproductive outcomes, including pregnancy loss, smaller litter sizes, or in offspring with abnormalities [14,15,90,91]. Relevant to the data here, postovulatory aged eggs have reduced MAPK3/1 activity associated with a range of membrane and cortical abnormalities and the above-mentioned propensity to undergo parthenogenetic activation [92][93][94][95][96][97][98][99][100]. Thus, what we observe here with MAPK3/1 pathway inhibition and the associated reduction in myosin-II function is consistent with changes that occur with postovulatory aging, suggestive of a tie between reduced MAPK3/1 activity and several of the changes observed in aged eggs.…”
Section: Discussionmentioning
confidence: 84%
“…Thus, the collagenase ZP removal method is a mild method with no observable harm to the oocytes that can simultaneously discriminate the spontaneously activated low quality oocytes from normal, young oocytes [16].…”
Section: Discussionmentioning
confidence: 99%
“…Eggs were collected in TYH-HEPES (Table 1) from oviducts at 13-15 h after hCG injection, which were referred to as young eggs. Eggs collected from oviducts at 26 h after hCG injection were referred to as post-ovulatory aged eggs [15][16][17]. Cumulus cells were removed by treatment with 5 min incubation in TYH-HEPES containing 0.05% hyaluronidase.…”
Section: Egg Collection (For Young and Aged Eggs)mentioning
confidence: 99%
“…Our past work showed that fertilization cone formation was delayed in eggs fertilized by ICSI [54], of note because ICSI-fertilized eggs were deficient in the ability to establish a membrane block to polyspermy [54][55][56]. We therefore speculated that prophase I oocytes could have differences in sperm-induced membrane and cortical remodeling; we examined this by low-vacuum scanning electron microscopy [76]. Control fertilized metaphase II eggs showed clear signs of membrane remodeling, with the formation of an amicrovillar patch over the site of sperm incorporation (Fig.…”
Section: Membrane and Cortical Changes Associated With Fertilization mentioning
confidence: 96%
“…Unfertilized and fertilized oocytes and eggs were prepared for scanning electron microscopy and viewed using an FEI Quanta 200 Environmental Scanning Electron Microscope with low-vacuum mode as previously described [76]. Micropipette aspiration to assess effective cortical tension was performed as previously described [77].…”
Section: Scanning Electron Microscopy and Micropipette Aspirationmentioning
confidence: 99%